Review on Practices and State of the Art Methods on Delineation of Ground Water Potential Using GIS and Remote Sensing - Silwal, Champak Babu; Pathak, Dinesh (Bulletin of the Department of Geology, 2018)
Due to global increase in human population, the groundwater has been extensively used to meet the water demand for domestic as well as agricultural purpose. The number of deep and shallow wells has increased exponentially. For these purpose the groundwater potential area has to be delineated so as to delineate the area for intervention for groundwater abstraction. The determination of groundwater potential with the aquifer characteristics is not always possible due to unavailability of secondary data and from financial aspect. The delineation of groundwater potential with the integration of GIS and Remote Sensing (RS) as well as with the aid of geophysical data could be an effective approach. Groundwater delineation in mountainous region uses different hydrogeologic parameters like rainfall, slope, elevation, drainage density, lineament density, lithology/geology, land use/land cover (LULC), soil, etc., whereas in case of alluvial basins, parameters like aquifer material, soil, LULC, water table, specific yield, storage coefficient, transmissivity, etc. are used. The assignment of weight for the factors and rank for their classes are important steps in the Groundwater Potential Mapping (GPM) using GIS overlay. The weights for the different parameters have to be assigned as per their role in groundwater occurrences. Different methods like Analytical Hierarchy Process (AHP), expert’s knowledge, probability weight approach, bivariate analysis, etc. have been used for assigning weights and ranks and the predicted potential need to be validated. Generally in mountainous aquifer, spring inventory forms the basic data for the verification. In addition, the aquifer characteristics like water table, yield, transmissivity can be used for the validation in flat lands. This method of delineation of groundwater potential is found to be appropriate with acceptable accuracy. Globally, there is increasing trend in the use of GIS and Remote Sensing for the identification of groundwater potential in recent time. Bulletin of Department of Geology, vol. 20-21, 2018, pp: 7-20